A potential new metabolite of gamma-hydroxybutyrate: sulfonated gamma-hydroxybutyric acid - Hanisch, Stephanie; Stachel, Nicole; Skopp, Gisela (International journal of legal medicine, 2016)
Detection of gamma-hydroxybutyric acid (GHB) became crucial in many clinical and forensic settings due to its increasing use for recreational purposes and drug-facilitated sexual assault. Its narrow window of detection of about 3-12 h in urine represents a major problem. Analogous to ethyl glucuronide, the recently identified GHB-glucuronide exhibits a longer window of detection than the parent drug. It appeared reasonable that a sulfonated metabolite of GHB (GHB-SUL) will also be formed. Due to the lack of an appropriate standard, GHB was incubated with a human liver cytosolic fraction to produce GHB-SUL. Following development of a liquid chromatography/tandem mass spectrometry (LC-MS/MS) assay to measure GHB and GHB-SUL, authentic urine samples (n = 5) were tested for GHB-SUL. These investigations revealed detectable signals of both GHB and GHB-SUL, strongly indicating that GHB is not only glucuronidated but also sulfonated. Given that sulfonated metabolites generally have longer half-life times than the corresponding free drugs, GHB-SUL may serve as a biomarker of GHB misuse along with its glucuronide.
Published online: 26 July 2015
Gesehen am 12.03.2020